Simulation of flow characteristics of acid fluid in fractures during acidizing and fracturing of carbonate rocks - Lim, Gareth Ryan (Nanyang Technological University, 2024)
The purpose of this study is to study the seepage characteristics of acid flow within a carbonate rock matrix during an acid fracturing process. Acid fracturing is a rock dissolution process that can be used to gain access to carbonate reservoirs which contain natural resources such as crude oil and natural gas. Acid is first injected into the carbonate rock matrix at specific initial conditions, where the acid then reacts with the carbonate rock in a chemical reaction to dissolve the rock. This reaction propagates cracks in the rock matrix and these cracks allow access to the carbonate reservoirs located within the rock matrix. For this project, the process is simulated in COMSOL Multiphysics under high temperature and pressure conditions to gain a better understanding of acid seepage characteristics. By better understanding the flow characteristics of acid, the efficiency of acid fracturing can be improved, which in turn increases the production of oil and gas. From the results, it was determined that inlet pressure, fluid viscosity, temperature, rock matrix and fracture permeability all have a significant effect on the parameters in the acid fracturing process. Increased inlet pressure produced decreased HCl and CO2 concentrations at the fracture, along with increased maximum pressure and velocity. Increased fluid viscosity resulted in reduced velocity, HCl and CO2 concentrations, while pressure remained constant. Increased temperature produced lower HCl and CO2 concentrations, while pressure and velocity remained unaffected. Increasing rock matrix permeability produced higher HCl and CO2 concentrations in the fracture path and faster velocity, while maximum pressure distribution increased in area. Lastly, increasing fracture permeability resulted in increased velocity, HCl and CO2 concentration area, while pressure remained unaffected. The results obtained from the simulations further emphasize the impact of adjusting parameters to further optimize the process of acid fracturing in carbonate rocks.